2016
DOI: 10.48550/arxiv.1611.02021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Decomposing the vertex set of a hypercube into isomorphic subgraphs

Abstract: Let G be an induced subgraph of the hypercube Q k for some k. We show that if |G| is a power of 2 then, for sufficiciently large n, the vertex set of Q n can be partitioned into induced copies of G. This answers a question of Offner. In fact, we prove a stronger statement: if X is a subset of {0, 1} k for some k and if |X| is a power of 2, then, for sufficiently large n, {0, 1} n can be partitioned into isometric copies of X.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…existence of a perfect H-packing in Q n : H has to be a subgraph of Q n ; and the order of H has to be a power of 2. Gruslys [5] showed that these two conditions are sufficient for large n, thus confirming a conjecture of Offner [12]. In fact, he showed that if H is an induced subgraph of Q k for some k and |H| is a power of 2, then there is a perfect packing of G into induced copies of H.…”
mentioning
confidence: 70%
See 4 more Smart Citations
“…existence of a perfect H-packing in Q n : H has to be a subgraph of Q n ; and the order of H has to be a power of 2. Gruslys [5] showed that these two conditions are sufficient for large n, thus confirming a conjecture of Offner [12]. In fact, he showed that if H is an induced subgraph of Q k for some k and |H| is a power of 2, then there is a perfect packing of G into induced copies of H.…”
mentioning
confidence: 70%
“…The task of finding an l-partition is quite simple. In fact, it follows directly from the analogous result in [5] and the fact that (P 2l ) n can be partitioned into copies of Q n . For the sake of completeness, we include the proof here.…”
Section: Lower Bound On the Number Of Uncovered Verticesmentioning
confidence: 82%
See 3 more Smart Citations